Asam Garam: A Short Film Screenplay Adapted from Dee Lestari’s Short Story About the Journey Through Grief - Deby Christi; Dwi Setiawan (Institute of Research and Community Outreach - Petra Christian University, 2026)
This creative work, a short film screenplay adapted from Dee Lestari’s short story Asam Garam, explores the experience of loss and its impact on an individual’s life, the journey through grief, and the process of overcoming grief toward acceptance. These elements are elaborated through a short film screenplay grounded in Kübler-Ross’s (2014) theory of loss and stages of grief, as well as the dual process model of coping with bereavement proposed by Stroebe and Schut (1999). The screenplay is also developed using the adaptation principles outlined by Hutcheon (2006) and Desmond and Hawkes (2006). The narrative centers on Gaspar, a skeptical journalist mourning the death of his father, who is assigned to interview the owner of a popular shop in Papua that sells a mysterious black salt said to make anyone cry without reason. His encounter with the shop owner gradually enables him to accept his loss. This story demonstrates that multiple losses can lead to a series of subsequent losses that shape an individual’s psychological wounds, that the grieving process varies across individuals and is inherently non-linear, and that crying can serve as an initial step toward healing.